Determinants of the Human Development Index (HDI) in Indonesia, 2014 - 2021 - Dwi Palupi Panglipuring Tyas; Ni Made Sukartini (MediaTrend, 2022)
Human development is a process of community change in improving the welfare andprosperity of their lives which includes aspects of health, education, economic andsocial aspects. This study aims to analyze the effect of protein intake, early marriage,health and educational facilities, unemployment, and MSMEs on HDI in Indonesia.The OLS and FEM model are used to estimate Indonesia’s 34 provinces panel dataset from 2014 in 2021. The study results show the life expectancy was affected byprotein consumption, number of hospitals, and health centers. The average length ofschooling is affected by the number of elementary, high school, and vocational schools and is influenced by the number of elementary and vocational school teachers. Gross Domestic Regional Product (GRDP) per capita is affected by unemployment rate and MSMEs. The increasing of protein consumption, early marriages evidences, number of health care provision, number of school are correlated on HDI. Furthermore, HDI is also affectef by the reduction of unemployment and number of MSMEs.